CIRCULATING TUMOR CELLS: WHERE WE LEFT OFF? - I. Kryvoshlyk (National Academy of Sciences of Ukraine and Palladin Institute of Biochemistry of the National Academy of Sciences of Ukraine., 2021)
Cancer metastasis and recurrence are the leading causes of cancer-related death. Tumor cells which leave the primary or secondary tumors and shed into the bloodstream are called circulating tumor cells (CTC). These cells are the key drivers of cancer dissemination to surrounding tissues and to distant organs. The use of CTC in clinical practice necessitates the deep insight into their biology, as well as into their role in cancer evasion of immune surveillance, tumor resistance to chemo- radio- and immunotherapies and metastatic dormancy.